(untitled) (Interdisciplinary Studies Journal, 2026)
The municipality of Pinheiral, located in the state of Rio de Janeiro, aims to universalize schooling for students with disabilities, global developmental disorders, and high abilities/giftedness, ensuring an inclusive education system. This study aims to comparatively analyze how this municipality has organized itself to comply with the recommendations of education legislation and the national education plan regarding laws addressing diversity and inclusion. We compared the provisions of the main law with how it relates to the municipality. As a result, Pinheiral has 30 schools where it has been committed to promoting inclusion, but the number of multifunctional resource rooms is still small. We conclude that inclusion has been developed slowly and depends on policies and the actors involved in the process, not only hypothetically, as we see in many situations where discourse differs from practice.